ANALISIS POTENSI LONGSOR LERENG BUKIT TUI KELURAHAN TANAH HITAM KOTA PADANG PANJANG SUMATERA BARAT MENGGUNAKAN APLIKASI SLIDE V6.0 - Yoszi Mingsi Anaperta; Septian Andika Putra (Universitas Negeri Padang, 2019)
Tui Hill is a limestone hill lined south of Padang Panjang. It is located between Rao-Rao Village and Tanah Hitam. Based on the results of investigations of researchers on the slopes of Bukit Tui limestone in the coordinates S0 ° 28'21.3